The Impact of a Digital Speaker on a Teacher's Interaction with a Child with Limited Functional Speech - Elsa Popich; Erna Alant (South African Journal of Communication Disorders, 1999)
This paper describes the impact of the implementation of a digital speaker and teacher training on the quality of a teacher's interaction with an AAC user. The data was obtained by recording and analysing classroom story time interactions. The types of utterances directed at each child in the class, the types of questions used as well as the messages recorded onto the digital speaker were determined for each research phase. There were four major phases in the research, namely, a pre-implementation phase, a post-implementation phase, a post-training phase and a post-withdrawal phase. The results indicated that the implementation of the digital speaker and the training of the teacher resulted in certain changes in the way that the teacher interacted with the AAC user. Utterance types such as answering and imitating were used more frequently after the implementation of the device. There was also a much greater variety in the teacher's use of questions as well as in the messages that were recorded onto the digital speaker after the five training sessions were completed. This study highlighted the importance of formal training for the communication partners of the AAC user. One of the most important communication partners of the school-aged AAC user is the classroom teacher.